The Impact of Labor, Unemployment, and Poverty on Economic Growth in Tarakan City - Nurul Atasya (one million dreams corporation, 2025)
This study aims to analyze the influence of labor, unemployment, and poverty on economic growth in Tarakan City. The method used is quantitative descriptive with time series data from 2013–2020 and multiple linear regression analysis using SPSS 25.0. The results show that partially, labor has no significant effect on economic growth, while unemployment and poverty have a significant effect. Simultaneously, these three variables have a significant effect on economic growth with a contribution of 55%. These findings provide policy implications for the government in designing strategies for labor absorption and poverty alleviation.